‘‘Click, Share, Da’wah: Spiritual Revolution at Your Fingertips’’ - Famuji, Untung; Kholis, Nur; Basit, Abdul; Malik, Ahmed Abdul (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This research investigates how digital accessibility, facilitated by “click and share” mechanisms, drives a spiritual revolution in Islamic da’wah practices among Indonesian Muslims. The study aims to explore the shifts in religious learning patterns and the evolution of individual spirituality within the rapidly advancing digital era. Employing a qualitative methodology, this study integrates digital ethnography and in-depth interviews with 30 participants, including digital preachers (da’i), active social media users, and individuals who have undergone spiritual transformation through online platforms. Thematic analysis was applied to uncover recurring patterns in digital spiritual engagement and the dynamics of transformation in these digital spaces. The findings reveal that the ease of access enabled by a simple “click” has redefined religious learning, shifting it from rigid, scheduled sessions to on-demand spiritual consumption. Meanwhile, the culture of “sharing” has fostered new forms of religious social validation. Digital da’wah has transformed from traditional, lengthy sermons into micro-content formats using memes, visuals, and personalized messages. The study proposes the theoretical concept of “fingertip spirituality” as a new paradigm for digital religious engagement, offering practical and theoretical implications for Islamic communication strategies in the digital age.